A comparative study on the press freedom in Malaysia and the United Kingdom / Noor Rafidah Mohammad Morzuki and Noor Rafidah Mohammad Morzuki - Mohammad Morzuki, Noor Rafidah; Mat Deris, Siti Farah (2006)
This research is about a comparison of press freedom between Malaysia and UK. In these new era, world of journalist in Malaysia become more complex and dilemma to deal with too many restriction and interference of government give the press a limited freedom in reporting news. This project is aim for the possibility to enforce UK law into Malaysia scenario does press can publish more news in public interest not only for certain political interest. This research did not touch about a sensitivity issues and political interest. This research about a press freedom generally. The aim of this research is to examine the scope and the limitation of Article 10 of Federal Constitution in Malaysia and Article 10 of European Convention of Human Rights incorporated with Section 12 of HRA. The writers also focus on the ground whether Government of Malaysia and UK is controlling their freedom.